Analysing the Institutional building for Solar Radiation and Photovoltaic Energy using AutoDesk-Revit. Issue 1 (1st February 2022) - Kumar, Mukul; Rawat, Paritosh; Maurya, Amit; Kumar, Ravinder; Bharadwaj, Ujjwal; Duggal, Prakhar
Abstract: Unconventional sources of energy like solar are not only green but sustainable too. Adopting sustainable sources of energy is a futuristic approach. Working in similar directions in current research, paper authors analyzed and modeled various aspects of an institutional building for solar energy suitability and efficiency by using Autodesk Revit software solar Plugin 2021. The various aspects of solar analysis such as sun path, PV potential and solar radiation value are observed and recorded. After ranging the different criteria like PV surface coverage and PV efficiency the mean energy cost tends to be reduced. Authors observed that the energy cost got reduced to 18.8$ from 24.3$.